2017
DOI: 10.1371/journal.pone.0183656
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal antigen screening by lay cadres using a rapid test at the point of care: A feasibility study in rural Lesotho

Abstract: IntroductionCryptococcal meningitis is one of the leading causes of death among people with HIV in Africa, primarily due to delayed presentation, poor availability and high cost of treatment. Routine cryptococcal antigen (CrAg) screening of patients with a CD4 count less than 100 cells/mm3, followed by pre-emptive therapy if positive, might reduce mortality in high prevalence settings. Using the cryptococcal antigen (CrAg) lateral flow assay (LFA), screening is possible at the point of care (POC). However, cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Nineteen studies reported outcomes among 353 CrAg-positive, asymptomatic PLHIV who were started on fluconazole prophylaxis [ 9 , 11 , 19 , 21 , 24–27 , 31 , 38 , 42 , 52 , 54 , 55 , 60–62 , 64 , 70 ], with clinical outcomes from one study [ 19 ] reported in a separate report [ 71 ]. Median follow-up time was 9 months (interquartile range, 6–12 months).…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies reported outcomes among 353 CrAg-positive, asymptomatic PLHIV who were started on fluconazole prophylaxis [ 9 , 11 , 19 , 21 , 24–27 , 31 , 38 , 42 , 52 , 54 , 55 , 60–62 , 64 , 70 ], with clinical outcomes from one study [ 19 ] reported in a separate report [ 71 ]. Median follow-up time was 9 months (interquartile range, 6–12 months).…”
Section: Resultsmentioning
confidence: 99%
“…MSF-supported hospitals usually have relatively high-quality care, consistent funding and resources, and patients with better access to services and ART. The fact that these results were seen even in MSF’s facilities implies that addressing advanced HIV will demand more: improved identification of treatment failure and symptomatic HIV patients in primary healthcare facilities and in the community, better point-of-care diagnostic technology (eg, TB-LAM and CrAg tests for opportunistic infections, or oral HIV self-tests), and patient tracing and psychosocial support for people who drop out of care or stop treatment [ 21 ]. The need remains for expanded access to routine VL testing to verify patients’ adherence and treatment efficacy, and for CD4 as an indicator of immunocompromise to better target opportunistic infection testing.…”
Section: Discussionmentioning
confidence: 99%
“…No studies to date have assessed the accuracy of the IMMY CrAg LFA for screening patients using a pipette to transfer finger-prick blood. However, in Lesotho, POC CrAg screening (without a laboratory-based reference standard) using a pipette identified 14/129 (11%) CrAg-positive patients with a CD4 count <100 cells/mm 3 , 12 of whom were asymptomatic at the time of testing(16).…”
Section: Discussionmentioning
confidence: 99%